Organizational Climate and Labor Performance of the National Institute of Civil Defense – INDECI - Penachi Valle, Nelson (2019)
This research article describes the correlation between the organizational climate and the work performance of the staff of the National Institute of Civil Defense, so an adequate work climate contributes to the achievement of the proposed goals, improves the quality of the service, the adverse does not contribute to the optimization of management and makes it difficult to achieve the planned objectives. The influence of the work environment on the performance of the employees of the institution, which are fundamental, is highlighted. Finally, as a result, there is a significant relationship, expressed through efficiency, effectiveness and quality, important aspects to be developed within the framework of institutional management.